Iodine and fertility: do we know enough?. Issue 2 (8th December 2020) - Mathews, Divya M; Johnson, Neil P; Sim, Robert G; O'Sullivan, Susannah; Peart, Jane M; Hofman, Paul L
Abstract: Iodine is a vital micronutrient and its importance in thyroid function is well established. However, abnormalities in iodine intake may also have other effects. In particular, iodine is taken up avidly by the ovary and endometrium. Iodine deficiency is associated with reduced fertility. The use of high iodine concentration contrast media has recently been shown to improve conception rates in couples with unexplained infertility (UI). We hypothesize that this improvement could be related to the iodine excess and mechanisms independent of its action on thyroid. In this article, the metabolism of iodine and its potential role in fertility will be discussed, including the impact of both iodine deficiency and excess states and the importance of iodine in normal fetal development. This will include insights from animal studies on the effect of iodine in the uterine and ovarian structural environment, hormonal milieu and immunological factors affecting implantation. We speculate that iodine may well have a role as a potential therapy for UI.